PEMBERDAYAAN MASYARAKAT MELALUI PENGEMBANGAN POTENSI DESA WISATA KETINGAN KABUPATEN SLEMAN - DI YOGYAKARTA - Supartini Supartini (JURNAL NASIONAL PARIWISATA, 2012)
Empowerment is the study discussed in this research and it is related to the potential development of tourism village of Ketingan Tirtoadi Mlati Sleman Yogyakarta Special Region. The objective of this research is to answer the problems as follows: first is how the community empowerment in tourism village of Ketingan; second how is the public re-sponse to community empowerment and third is what are the supports and obstacles in the implementation of community empowerment.This research is an empowering community research which is observing the implemen-tation of empowerment by using library study and field studies as a means of data collec-tion. The source of the data was obtained from the research site of Ketingan tourism village and taken from the competence informant as well as from the relevance and sup-porting government institution and private institutions. The data analysis was done by using qualitative analysis with descriptive approach which elaborates the data and the fact obtained from the research or the field of the research.The finding of the research shows that the community empowerment in Ketingan tour-ism village has already ran smoothly although it has not reached the independence level. The potential development was conducted by the management which applies the tour-ism attraction, accommodation/home stay. The planning to form the tourism package which adopts the cluster management model needs to be considered seriously since it will give benefit and it can increase the involvement of UKM and the members of the community besides that it can be one of the tourism attractions. Most of the community members understand the meaning of empowerment so that the management finds it easily to implement and socialize the planned activities, although there are some con-straints relating to the funding and the human resource.